Effectiveness of foot massage on sleep quality among post-surgical patients in Dr. H Abdul Moeloek Hospital, Lampung-Indonesia - Fictor Yusman Agung; Aprina Aprina; Titi Astuti (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Republic of Indonesia's Health Survey in 2009, finding that the therapy through surgery was the 11th, because of surgery conduct in Indonesia in 2012 reached 1.2 million. The problem that often arises after surgery is a sleep disorder, pain and uncomfortable.Purpose: To identify effectiveness of foot massage on sleep quality among post-surgical patients in Dr. H Abdul Moeloek Hospital, Lampung-IndonesiaMethods: The design of this research is quasy experiment with pretest design with posttest with control group design. This type of quantitative research using consecutive sampling techniques. The population in the study were 64 participants. The analysis used is the dependent and independent t test.Results: Indicating the average score of sleep quality in the control group post intervention 9.12. Whereas sleep quality in the intervention group was obtained at 4.78 post intervention. A p-valeu 0.000 was obtained which showed differences in sleep quality scores both groups and interventions.Conclusion: There is effectiveness of foot massage on sleep quality among post-surgical patients in Dr. H Abdul Moeloek Hospital, Lampung-Indonesia. It is recommended that hospitals can include foot massage therapy as an alternative therapy in overcoming sleep disorders in postoperative clients.